Herniation of the appendix into the umbilical cord complicating umbilical vessel cannulation - Mohammad Mahdi Khazravi; Marjan Joodi; Shiva Ghaderifar; Mehdi Fathi; Reza Nazarzade; Hossein Mohsenzade; Maryam Joudi (Elsevier, 2019)
Umbilical catheters (UC) have become the most common way to access neonatal veins and arteries especially after the increasing the number of preterm newborns. Significant clinical complications have been reported with this increased usage of UC. We present a rare complication of umbilical catheterization in a newborn with asphyxia that had meconium discharge after UC. Keywords: Umbilical catheter, Complication